ANALISIS PENCATATAN KEUANGAN DAN IMPLEMENTASI PENGGUNAAN APLIKASI AKUNTANSI BERBASIS VBA EXCEL PADA CV XYZ - Vanesia Rachmananda, Thalia; Susanti, Ari (JURNAL LENTERA AKUNTANSI, 2025)
The low level of understanding of financial recording and the high cost of bookkeeping applications make it difficult for many MSMEs to switch to a more efficient and structured digital recording system. This situation has quite serious impacts because the lower the quality of a company's financial reports, the lower the company's financial condition. CV XYZ is one of the MSMEs that still relies on simple, less systematic, accurate, and efficient recording. This study aims to improve the accuracy and efficiency of CV XYZ's financial recording through the implementation of a VBA Excel-based accounting application. This study uses a qualitative method with a descriptive approach. The data for this study were obtained through in-depth interviews and direct observation. The results of this study indicate that the use of a VBA Excel-based accounting application at CV XYZ can significantly overcome the company's financial recording problems, especially in terms of efficiency, accuracy, and ease of access to financial information.